Effect of Two Combined Oral Contraceptives on Serum Lipid Profile (Bangladesh Medical Journal, 2014)
Alterations in the composition of the plasma lipids caused by estrogens are characterized by an increase in the high-density lipoproteins (HDL) and plasma triglyceride, a slight reduction in the low-density lipoproteins (LDL), and a reduction in total plasma cholesterol levels. Oral Contraceptive pills(OCP) having different doses of hormones may affect blood lipids differently. The present study was designed to see the effect of two combined oral contraceptives on lipid levels. 68 females of the reproductive age who were advised to do lipid profile before and after using oral contraceptives were included in this study. One group of 38 females was advised to take 30 mcg of oestrogen in the form of Ethinylestradiol and 150 mcg of progesterone in the form of Desogestrel while another group of 38 females was advised to take 0.05 mg of oestrogen in the form of Ethinylestradiol and 1 mg of progesterone in the form of Lynestrenol. Cholesterol(P